Neonatal sepsis as a risk factor for neurodevelopmental changes in preterm infants with very low birth weight, - Ferreira,Rachel C. (2014)
OBJECTIVE:to evaluate neonatal sepsis as a risk factor for abnormal neuromotor and cognitive development in very low birth weight preterm infants at 12 months of corrected age.METHODS:this was a prospective cohort study that followed the neuromotor and cognitive development of 194 very low birth weight preterm infants discharged from a public neonatal intensive care unit. The Bayley Scale of Infant Development (second edition) at 12 months of corrected age was used. The outcomes were the results of the clinical/neurological evaluation and the scores of the psychomotor development index (PDI) and mental development index (MDI) of the Bayley Scale of Infant Development II. The association between neonatal sepsis and neuromotor development and between neonatal sepsis and cognitive development was verified by logistic regression analysis.RESULTS:mean birth weight was 1,119 g (SD: 247) and mean gestational age was 29 weeks and 6 days (SD: 2). Approximately 44.3%(n = 86) of the infants had neonatal sepsis and 40.7% (n = 79) had abnormal neuromotor development and/or abnormal psychomotor development index (PDI < 85) at 12 months of corrected age. On the mental scale, 76 (39.1%) children presented abnormal cognitive development (MDI < 85). Children with neonatal sepsis were 2.5 times more likely to develop changes in neuromotor development (OR: 2.50; CI: 1.23-5.10). There was no association between neonatal sepsis and cognitive development impairment.CONCLUSION:neonatal sepsis was an independent risk factor for neuromotor development impairment at 12 months of corrected age, but not for mental development impairment.